Phase Analysis of Nickel Superalloy Inconel 738 LC - Zdenek Jonsta; Petr Jonsta; Katerina Konecna; Miriam Gabcova (Communications - Scientific letters of the University of Zilina, 2010)
Alloys of INCONEL (hereinafter IN) type play an important role among superalloys, used for the components of aircraft engines, gas turbinesand turbo blowers. It is cast material which is alloyed in a complex manner on the Cr–Al–Mo–Ti–Nb–Zr basis.The presented work made a detailed microstructural analysis of cast nickel superalloy IN 738 LC after heat treatment to the required quality and after long term annealing at the temperature of 850 °C and at dwell of 100, 500, 1000, 5000 and 10 000 hours.Higher level of alloying of this alloy shows the higher level of a segregation activity. This may lead to high temperature exploitation to the development of microsegregation processes, connected to possible precipitation of carbidic or some variants of intermetallic phases [1]. Several strengthening mechanisms take place here, and a main strengthening is the precipitation strengthening by coherent precipitates of an intermetallicphase Ni3Al, or Ni3(Ti, Al) [2].The objective of the presented microstructural analysis consisted in a more detailed understanding of investigated nickel superalloy from a technical applicability viewpoint.